THERMAL, WATER ABSORPTION, AND MECHANICAL PROPERTIES OF POLYPROPYLENE – GRAFT – MALEIC ANHYDRIDE COMPATIBILIZED POLYPROPYLENE / POLYCARBONATE BLENDS - MAT SHAYUTI, MUHAMMAD SHAFIQ (2012)
This work investigates the effect of blending polycarbonate (PC) into polypropylene (PP) matrix polymer on properties namely thermal, water absorption, and mechanical. The blends, containing 0% to 35% of polycarbonate and 5% compatibilizer, were compounded using twin – screw extruder and fabricated into standard tests samples using injection or compression molding. The compatibilizer used was polypropylene-graft-maleic anhydride (PP-g-MA). Thermogravimetric analysis (TGA) showed improved thermal degradation temperature of the blends compared to PP. Thermal conductivities for the blends were found to be in between PP and PC, and can be predicted by Hanshin – Shtrikman model with considerable accuracy. In water absorption test, specimens were immersed in distilled water at 23oC and 100oC. In 23oC immersion, PC showed the highest absorption at 0.362 wt%, while PP was the lowest at 0.064 wt%. The blends demonstrated transitional absorption value between PP and PC. In 100oC immersion, 90/5/5, 80/15/5, and 70/25/5 compositions (PP/PC/PP-g-MA) exhibited lower absorption than PP, indicating enhanced long – term degradation resistance in water compared to PP.